Determinants Of Sino-US Relations - رولا غازي اسماعيل; دريد العيسى; رانيا محجازي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The Sino-American relations are characterized by a large degree of change, as it is described as a complex relationship full of contradictions. Despite the competition between the Chinese and American powers in many fields, they need each other in other areas. The research aims to study the potentials of China and the United States of America in international hegemony .And identifying areas of cooperation and competition between them, in addition to studying the determinants of Sino-US relations. The researcher reached several conclusions, the most important of which is that the bilateral relations between China and the United States of America were distinguished by strangeness, as each side views the other as neither an enemy nor a friend, and that the common interests between the two countries are what guided the relationship between them, not friendship or political ideology.